Fetal Programming of Body Composition, Obesity, and Metabolic Function: The Role of Intrauterine Stress and Stress Biology. (10th May 2012) - Entringer, Sonja; Buss, Claudia; Swanson, James M.; Cooper, Dan M.; Wing, Deborah A.; Waffarn, Feizal; Wadhwa, Pathik D.
Abstract : Epidemiological, clinical, physiological, cellular, and molecular evidence suggests that the origins of obesity and metabolic dysfunction can be traced back to intrauterine life and supports an important role for maternal nutrition prior to and during gestation in fetal programming. The elucidation of underlying mechanisms is an area of interest and intense investigation. In this perspectives paper we propose that in addition to maternal nutrition-related processes it may be important to concurrently consider the potential role of intrauterine stress and stress biology. We frame our arguments in the larger context of an evolutionary-developmental perspective that supports roles for both nutrition and stress as key environmental conditions driving natural selection and developmental plasticity. We suggest that intrauterine stress exposure may interact with the nutritional milieu, and that stress biology may represent an underlying mechanism mediating the effects of diverse intrauterine perturbations, including but not limited to maternal nutritional insults (undernutrition and overnutrition), on brain and peripheral targets of programming of body composition, energy balance homeostasis, and metabolic function. We discuss putative maternal-placental-fetal endocrine and immune/inflammatory candidate mechanisms that may underlie the long-term effects of intrauterine stress. We conclude with a commentary of the implications for future research and clinical practice.